ANALISIS SUMBER MOLEKUL, PENYEBAB KONTAMINASI DAN PENANGGULANGAN RESIDU PESTISIDA PADA KAYU MANIS (Cinnamomum burmannii) DI PROVINSI JAMBI DAN SUMATERA BARAT - Fachri, Muhammad (Universitas Andalas, 2025)
This study aims to analyze the types of dominant contaminant molecules, identify the factors causing contamination, compare pesticide residue characteristics between regions, examine the relationship between residues and cultivation or processing practices, and formulate mitigation strategies for pesticide residues in cinnamon (Cinnamomum burmannii) commodities in Jambi and West Sumatra Provinces. The analysis revealed seven dominantly detected contaminant molecules, namely phenylphenol 2-, propamocarb, chlorpyrifos, fipronil, fipronil (sum), isoprocarb, and diethyl-m-toluamide (DEET), each with a detection frequency above five percent. These molecules are suspected to originate from pesticide applications, environmental pollution, and human activities. Statistical analysis using the Mann-Whitney U Test showed that 12 molecules had significantly higher residue levels in samples from West Sumatra compared to Jambi (p < 0.05), including ametryn, anthraquinone, carbofuran and its fractions, ethion, ethylene oxide, griseofulvin, nicotine, propamocarb, chlorpyrifos, DEET, and isoprocarb, indicating a clear regional difference. Jambi samples classified as high-grade had lower residues, reflecting that high quality can be achieved through sustainable farming practices such as integrated pest management and natural drying, rather than intensive chemical treatments. These findings suggest a negative correlation between visual quality and residue levels. Recommended mitigation strategies include the application of IPM, farmer education, post-harvest washing and drying, and environmental remediation. The 2021–2025 trend shows residue fluctuations peaking in 2023 before declining, highlighting the importance of regular monitoring. This research provides a scientific basis to support food safety, sustainable production, and enhance the export competitiveness of Indonesian cinnamon Keywords- pesticide residues; cinnamon; cinnamomum burmannii; Jambi; West Sumatra